Subclinical atrial fibrillation - what is the risk of stroke? - Plasek, Jiri; Taborsky, Milos (Biomedical papers, 2019)
Atrial fibrillation is the most common arrhythmia and as such, it has become a significant public health issue due to its impact on patient morbidity and mortality. The prevalence of atrial fibrillation (AF) almost doubled in the last decade, being currently 2% in unselected patient populations. Its occurrence varies with age (present in almost 20% of octogenarians) and concomitant diseases. The most prevalent concomitant diseases are hypertension, diabetes, heart failure, renal failure, and cognitive decline. Cognitive decline or stroke may be actually the first manifestation of undiagnosed atrial fibrillation. In the majority of cases, atrial fibrillation is more of a syndrome than a disease in itself, with a multitude of etiologic factors and mechanisms. The risk of cardioembolic stroke increases with the number of comorbidities and age. The overall age-adjusted risk of stroke in patients with atrial fibrillation is 5 times higher than in the general population. Nowadays, the detection of asymptomatic episodes of atrial fibrillation by cardiac electronic implantable devices (CIED), referred to as device detected or subclinical atrial fibrillation, has opened new frontiers in AF management. The risk of stroke and subsequent need for anticoagulation treatment in this group of patients with device detected AF is however not clear. Here, we will review the literature to determine the association of subclinical atrial fibrillation with the risk of stroke.
Keywords: arrhythmia; subclinical atrial fibrilation